ISIS: Past, Present, and Future - Azoulay, Ronnie (Przegląd Strategiczny, 2016)
The main purpose of this article is to examine the causes which led to the establishment of ISIS. In addition, this text aims to get to the root of ISIS’s ideology and analyze step-by-step the driving factors and circumstances that led to the emergence of the Islamic State. Moreover, it purports to examine the dichotomous relationship between ISIS and al-Qaeda, and finally examine where the west and the Muslim world are headed.